Approved estimate and budget speeches - Bauchi State Government; Bauchi State Government (Bauchi : Bauchi state government Printer, 1993)
This is the approved current revenue and capital estimates of the Bauchi State Government of Nigeria for the fiscal year 1993.
lje 5/3/19
Arch.
Keywords: Public finance; Budget; Finance, Public -- Nigeria; Nigeria -- Bauchi State